Design, imaging and performance of 3D printed open‐cell architectures for porous electrodes: quantification of surface area and permeability. Issue 7 (6th May 2021) - Kaishubayeva, Nazira; Ponce de León, Carlos; Walsh, Frank C; Arenas, Luis F
Abstract: BACKGROUND: The development of new open‐cell porous electrodes for electrochemical flow cells and reactors is demonstrated through the application of 3D printing. The properties of diverse architectures were investigated, including rectangular, circular, hexagonal and triangular cells with linear porosity grades of 10, 20 and 30 pores per inch (ppi). Specimens were digitally designed, then 3D printed in stainless steel via selective laser melting. After being examined using scanning electron microscopy, they were characterized in terms of volumetric surface area and porosity with the aid of X‐ray computed tomography. Pressure drop measurements were performed over a range of mean linear velocity and Reynolds number, allowing the estimation of Darcy's friction factor and permeability. RESULTS: Volumetric surface area estimated from tomography scans was ≤36% higher than the nominal values owing to surface roughness and post‐processing algorithms. By contrast, volumetric porosity obtained by tomography agreed fully with measured values. Triangular architectures afforded additional surface area both digitally and according to tomography. The largest pressure drop was found in circular materials, the triangular ones showing the lowest. The 20 ppi triangular architecture had a volumetric surface area of ≈44.5 cm −1 and a permeability of 2.31 × 10 −5 cm 2 . CONCLUSION: Triangular architectures were preferred as a consequence of their favourable combination of high surface area and high permeability with low mass and reduced digital complexity. This provides a strategy to initiate the optimization of 3D printed porous electrodes for electrochemical flow cells and reactors in novel and niche applications. © 2021 The Authors. Journal of Chemical Technology and Biotechnology published by John Wiley & Sons Ltd on behalf of Society of Chemical Industry (SCI).